ANALISIS HUKUM TERHADAP TINDAK PIDANA PEMBUNUHAN BERDASARKAN PASAL 338 KUHP (STUDI KASUS PUTUSAN NOMOR 9/PID.B/2023/PN.DPK) - Johanes; Rineke Sara; Titik Sugianti (Constitutum: Jurnal Ilmiah Hukum, 2025)
The crime of murder is an act committed by a person or group of people who intentionally take or take the life of another person. Murder perpetrators are often found in adolescence. One form of juvenile delinquency is brawls, the impact of which can cause serious injuries to the point of taking the life of another person. The perpetrators of brawls that cause the loss of life of another person can be categorized as perpetrators of the crime of murder. This study discusses the application of the elements of the crime of murder based on Article 338 of the Criminal Code in the case of Decision Number 9/Pid.B/2023/PN.Dpk and whether the decision has provided a sense of justice. This study uses a normative juridical research method. The results of the study explain that the application of the elements of the crime of murder based on Article 338 of the Criminal Code in Decision Number 9/Pid.B/2023/PN.Dpk is appropriate because the actions committed by the Defendant Indra Beni Saputra alias Beni Bin Mulyadi contain the elements of whoever and the element of intentionally taking the life of another person. With the fulfillment of these elements, the Panel of Judges sentenced the Defendant to 9 (nine) years in prison. The decision handed down by the Panel of Judges has provided a sense of justice, this can be seen from the Panel of Judges' considerations where the Defendant committed assault using a sharp weapon which caused the victim's death, and is supported by evidence in the form of a sickle and evidence from the results of the Visum Et Repertum made by Citra Medika Depok Hospital which conducted an external examination.